2021
DOI: 10.1111/1541-4337.12836
|View full text |Cite
|
Sign up to set email alerts
|

Acylated anthocyanins: A review on their bioavailability and effects on postprandial carbohydrate metabolism and inflammation

Abstract: Anthocyanins, the natural red and purple colorants of berries, fruits, vegetables, and tubers, improve carbohydrate metabolism and decrease the risk factors of metabolic disorders, but their industrial use is limited by their chemical instability. Acylation of the glycosyl moieties of anthocyanins, however, changes the chemical properties of anthocyanins and provides enhanced stability. Thus, acylated anthocyanins are more usable as natural colorants and bioactive components of innovative functional foods. Acy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 334 publications
(477 reference statements)
1
60
0
Order By: Relevance
“…Indeed, the proportions and the concentrations of acylated anthocyanins are variable across the pigmented potato varieties. However, all the anthocyanins under investigation has been detected in our samples, thus supporting existing results [ 41 ]. Numerous factors may influence the occurrence and accumulation of pigments in the flesh of potatoes [ 42 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Indeed, the proportions and the concentrations of acylated anthocyanins are variable across the pigmented potato varieties. However, all the anthocyanins under investigation has been detected in our samples, thus supporting existing results [ 41 ]. Numerous factors may influence the occurrence and accumulation of pigments in the flesh of potatoes [ 42 ].…”
Section: Resultssupporting
confidence: 92%
“…Additionally, the acylated forms may be commonly linked to the rutinose, the most common glycosyl moiety, in position C3 [ 7 ], but also to other sugar moieties such as glucose, rhamnose, xylose, and arabinose. Jokioja et al [ 41 ] described how the glycosyl moieties and the acylation influenced the chemical proprieties of the acylated anthocyanins, such as the stability of these compounds [ 41 ]. It has been reported that the different trend in the accumulation of anthocyanins in red-skinned and purple-fleshed varieties is a noteworthy factor in determining the tuber coloration patterns and the differentiation between the two pigmented groups [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical and biofunctionalization are currently two strategies for the modification of nanoparticles. In addition, these advanced nanotechnologies assist the stabilization of anti-cancer drugs, which improve the bioavailability and controlled release ( Chen and Stephen Inbaraj, 2019 ; Jokioja et al, 2021 ; Rashwan et al, 2021 ; Shen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%